Silicon-based tribovoltaic nanogenerators: Surface chemistry isotope effect on device performance and durability - Xin Lyu; Melanie Macgregor; Nadim Darwish; Simone Ciampi (Friction)
Triboelectric nanogenerators (TENGs) are advanced devices designed to harness mechanical energy from various sources such as vibrations, friction, or shear and convert it into electrical energy. Schottky-based tribovoltaic nanogenerators (TVNGs) are a type of TENG that incorporates a semiconductor–metal barrier, known as a Schottky barrier, into their design. This barrier aids in rectifying the generated electrical output, eliminating the need for external current rectification circuits. Further, silicon-based Schottky TVNGs can leverage existing surface functionalization procedures to improve device output and durability. Almost without exception, these procedures commence with an oxide-free and hydrogen-terminated silicon surface (Si–H). Replacing hydrogen with its heavier isotope deuterium (Si–D) does not hinder access to established surface chemistry procedures, and based on previous reports the isotope exchange is likely to improve resistance of the non-oxide semiconductor against its anodic decomposition. In this report we have developed the optimal surface chemistry procedures for preparing Si–D surfaces and explored to what extent this isotope effect translates into improved performances and durability of Schottky TVNGs. Our findings reveal that the maximum current output of TVNGs constructed on Si–D Si (111) crystals is comparable to that of mainstream Si–H devices. Additionally, we highlight a generally higher density of surface electrical defects in Si–D compared to Si–H, and verify the contribution of a flexoelectric term to the mechanic-to-electrical energy conversion mechanism. Ultimately, our experiments demonstrate that the primary advantage of replacing hydrogen with deuterium lies in enhancing device longevity.